The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1073/pnas.82.24.8705
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical secretion of prorenin during the menstrual cycle: synchronization with luteinizing hormone and progesterone.

Abstract: Plasma prorenin, a high molecular weight precursor form of renin, (renin, EC 3.4.23.15; old number, EC 3.4.99.19), was measured three times weekly in normal young women during the menstrual cycle and was related to changes in luteinizing hormone, estradiol, and progesterone. In all subjects a stable baseline level of prorenin occurred during the follicular phase. Then, simultaneously or soon after the luteinizing hormone peak, plasma prorenin consistently increased about 2-fold. Baseline prorenin ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…Sealey and her group have also demonstrated that plasma prorenin peaks shortly after the luteinizing hormone peak during the normal menstrual cycle (24). These data strongly suggest gonadotropins may regulate theca cell renin production, as they appear to regulate Leydig cell renin production (25).…”
Section: Discussionmentioning
confidence: 66%
“…Sealey and her group have also demonstrated that plasma prorenin peaks shortly after the luteinizing hormone peak during the normal menstrual cycle (24). These data strongly suggest gonadotropins may regulate theca cell renin production, as they appear to regulate Leydig cell renin production (25).…”
Section: Discussionmentioning
confidence: 66%
“…Studies of the regulation of active renin and prorenin secretion were performed in 32 normal human volunteers who ranged in age from 21 to 56 yr. Only male subjects were used to avoid the potential confounding effects of variation in prorenin levels throughout the menstrual cycle (20 was the same on both diets. Samples for plasma renin measurements were obtained at the end of the period of equilibration.…”
Section: Subjectsmentioning
confidence: 99%
“…The process, apparently via the ovarian follicle, doubles the concentration of plasma prorenin. 70 - 71 There appears to be no renin secretion from the ovary, and there is no increase in plasma renin during the surge of ovarian prorenin secretion, suggesting that the ovarian prorenin system functions independently of plasma renin.…”
Section: -65mentioning
confidence: 99%